Multiple‐parameter reconfiguration in a single planar ultra‐wideband antenna for advanced wireless communication systems. Issue 11 (1st August 2014) - Aboufoul, Tamer; Chen, Xiaodong; Parini, Clive G.; Alomainy, Akram
Abstract : A compact frequency, pattern and polarisation reconfigurable planar ultra‐wideband antenna is presented. The antenna is frequency reconfigurable to allow flexible functionality such as limiting the impact of out‐of‐band interferers if required in certain applications. Moreover, it provides basic pattern reconfiguration to enhance the scanning or the communication performance in future wireless applications by sensing interferers in the space domain and achieving pattern diversity to mitigate fading and increase signal‐to‐noise ratio. Another special feature of the proposed antenna is that its polarisation is reconfigurable at specific frequencies to generate circular polarised (CP) radiation. The antenna performance characteristics are verified through parametric simulations and measurements. The proposed antenna presents significant degrees of freedom in providing reconfigurable properties in frequency, radiation patterns and polarisation as compared to standard single‐parameter reconfigurable antennas; therefore providing a flexible radio front‐end for smart radio and wireless applications such as cognitive radio.